Fracture formation in vitrified thin films of cryoprotectants - Rabin, Yoed (2006)
As a part of an ongoing effort to study the continuum mechanics effects associated with cryopreservation, the current report focuses on fracture formation in vitrified thin films of cryoprotectant agents. The current study combines experimental observations with continuum mechanics analysis. Experimental results have been developed using a new imaging device, termed a “cryomacroscope”, which has been recently presented by the current research team. A newly developed liquid nitrogen-based cooling stage is presented in this paper. The samples under investigation are 0.5 ml droplets of cryoprotective agents, having a characteristic diameter of 20 mm and a characteristic thickness of 1.5 mm. Tested samples included dimethyl sulfoxide (DMSO) in a concentration range from 6M to 8.4M, and the cryoprotectant cocktails VS55 and DP6. Some samples contained small bovine muscle segments, having a characteristic dimension of 1 mm, in order to study stress concentration effects. Experimental results show that the onset of fracturing in vitrified films of cryoprotectants is very consistent, occurring over a small temperature range. Fracture pattern, however, was affected by the cooling rate. The presence of tissue segments did not affect the onset temperature of fracture, but affected the fracture pattern. The continuum mechanics analysis solidified the hypothesis that fracture is driven by thermal stress, not by temperature per se, and allowed fracture strain to be inferred from observed fracture temperature. In conjunction with the current report, additional photos of fracture formation in thin films are available at http://www.me.cmu.edu/faculty1/rabin/CryomacroscopyImages02.html.